Computer vision and graphics : International Conference, ICCVG 2018, Warsaw, Poland, September 17-19, 2018, Proceedings /: International Conference, ICCVG 2018, Warsaw, Poland, September 17-19, 2018, Proceedings. (2018) - Unknown
No abstract available